Complete utilization of maternal and child health continuum of care among mothers of children aged 9–18 months in Habru district, Northeast Ethiopia - Habtamu Asefa; Mastewal Arefaynie; Mulugeta Desalegn; Birhanu Wagaye; Tadesse Gure Eticha; Dawit Firdisa (Clinical Epidemiology and Global Health)
Background: The maternal and child health (MCH) continuum of care is crucial for reducing maternal and child mortality. However, MCH service utilization in Ethiopia remains low. This study aimed to assess the utilization of the MCH continuum of care and identify associated factors among mothers in Habru district, northeast Ethiopia. Methods: A community-based cross-sectional study was conducted from January 10 to February 17, 2023. A multi-stage sampling method was used to select mothers with children aged 9–18 months. Data were collected using an interviewer-administered questionnaire and analyzed using SPSS version 26. Results: The prevalence of mothers who completed the MCH continuum of care was 25.3 % (95 % CI: 22.2 %, 28.5 %). Factors significantly associated with completion included education level, residence, access to healthcare within 60 min, early initiation of antenatal care (ANC), awareness of MCH services, mode of delivery, and birth preparedness planning. Conclusion: MCH continuum of care completion remains low in the study area. Education, early initiation of ANC, and awareness of MCH services were significant determinants. Strengthening these factors through targeted interventions is crucial to improve MCH service utilization in the region.